Efektivitas Edukasi menggunakan Video terhadap Peningkatan Pengetahuan dan Keterampilan Sadari pada Siswi Kelas XI di MAN 2 Yogyakarta - Inayah Rosmayanti; Sri Lestari (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Breast cancer is a serious health problem among women, with incidence and mortality rates that continue to rise. The disease is often detected at an advanced stage due to low levels of awareness, knowledge, and skills related to early detection. Among adolescent girls, particularly high school students, knowledge and skills regarding Breast Self-Examination (BSE) remain limited. This is largely due to restricted access to health information, a lack of targeted educational initiatives, and learning methods that are insufficiently engaging. BSE is a simple and effective early detection method that can be performed independently beginning in adolescence. Video-based education is considered an effective tool for enhancing adolescents’ understanding. This study aims to determine the effectiveness of video-based education in improving knowledge and BSE skills among Grade XI female students at MAN (State Islamic Senior High School) 2 Yogyakarta. This study employed a pre-experimental design using a one-group pre-test and post-test approach. The study population consisted of all Grade XI female students at MAN 2 Yogyakarta, with a sample of 59 students selected through purposive sampling on predetermined inclusion criteria. The intervention involved a single session of a BSE educational video lasting approximately seven minutes. It was conducted in 15 groups, with each group accompanied by one facilitator. Data were analyzed using the nonparametric Wilcoxon statistical test. The Wilcoxon test results showed a p-value of 0.000 (p < 0.05) for both knowledge and skills variables, indicating a statistically significant improvement between the pre-test and post-test scores. In conclusion, video-based education was proven effective in improving knowledge and BSE skills among Grade XI female students at MAN 2 Yogyakarta. Future researchers are encouraged to assess BSE skills using a structured checklist based on standardized evaluation criteria.